2016
DOI: 10.1038/bjc.2016.316
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and hormonal factors in relation to survival and platinum resistance among ovarian cancer cases

Abstract: Background: Ovarian cancer survival is poor, particularly for platinum-resistant cases. The previous literature on pre-diagnostic reproductive factors and ovarian cancer survival has been mixed. Therefore, we evaluated pre-diagnostic reproductive and hormonal factors with overall survival and, additionally, platinum-chemotherapy resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 33 publications
0
32
2
Order By: Relevance
“…In the current study, parity per se (but not increasing parity or age at first birth) was associated with better prognosis in contrast to most previous studies that have generally shown no significant association between parity and survival (Besevic et al , 2015; Poole et al , 2016; Shafrir et al , 2016). Recent observational studies have shown that parity is associated with decreased risk of type I tumours (i.e., low-grade subtypes; Fortner et al , 2015) as well as with less aggressive subtypes (i.e., survived ⩾3 years; Poole et al , 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the current study, parity per se (but not increasing parity or age at first birth) was associated with better prognosis in contrast to most previous studies that have generally shown no significant association between parity and survival (Besevic et al , 2015; Poole et al , 2016; Shafrir et al , 2016). Recent observational studies have shown that parity is associated with decreased risk of type I tumours (i.e., low-grade subtypes; Fortner et al , 2015) as well as with less aggressive subtypes (i.e., survived ⩾3 years; Poole et al , 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…The authors of the review concluded that overall the data were sparse, and whereas reproductive or hormonal factors were likely not strong predictors of outcome, body size was among the most studied and represented a lifestyle factor that may favourably influence prognosis. Since this review, one additional work evaluated the association of reproductive and hormonal factors on survival, in data from the New England Case-Control Study of Ovarian Cancer that included prediagnostic information on 1649 ovarian cancer patients and 911 all-cause deaths and reported improved survival for endometriosis and for HRT use (Shafrir et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although age at menarche was not significantly related to the risk of ovarian cancer overall, later age at menarche was associated with worse EOC survival. 29,30 It is still unclear whether an older age of menarche is associated with EOC considering the lifetime ovulation factor in OC etiology. Further studies are necessary to confirm possible interactions in larger independent populations.…”
Section: Discussionmentioning
confidence: 99%